2019
DOI: 10.1177/0018720819852509
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Muscular Fatigue From Static Posture Concurrently Reduces Cognitive Attentional Resources

Abstract: Objective The goal of this work is to determine whether muscular fatigue concurrently reduces cognitive attentional resources in technical tasks for healthy adults. Background Muscular fatigue is common in the workplace but often dissociated with cognitive performance. A corpus of literature demonstrates a link between muscular fatigue and cognitive function, but few investigations demonstrate that the instigation of the former degrades the latter in a way that may affect technical task completion. For example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Prolonged physical effort can lead to fatigue and a reduction in physical work (Gawron et al, 2001). Several studies have also supported a relationship between the physical load, fatigue, and cognition (Tomes et al, 2017;Stephenson et al, 2019). The physical effort to carry body armor resulted in diminished higher-level executive processing, which can include attentional control, working memory, and cognitive flexibility (Roberts and Cole, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Prolonged physical effort can lead to fatigue and a reduction in physical work (Gawron et al, 2001). Several studies have also supported a relationship between the physical load, fatigue, and cognition (Tomes et al, 2017;Stephenson et al, 2019). The physical effort to carry body armor resulted in diminished higher-level executive processing, which can include attentional control, working memory, and cognitive flexibility (Roberts and Cole, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…This muscle fatigue is influenced by task repetition and force (Ferguson et al, 2013). Muscle fatigue resulting from static posture reduces the user's cognitive attentional resources and could therefore have an effect on the quality of the work result (Stephenson et al, 2020). In addition, excessive vibration stress can lead to long-term illnesses, also known as hand-arm vibration syndromes (HAVS).…”
Section: Introductionmentioning
confidence: 99%
“…The nature of construction requires workers to maintain high level of concentration which can cause mental fatigue (Ko et al , 2017). The relationship between physical and mental fatigue was investigated for the construction industry and results indicated that muscular fatigue in specific regions can negatively affect attentional capabilities of individuals (Stephenson et al , 2019). However, no conclusive results were found as a negative impact of muscular fatigue on mental fatigue.…”
Section: Introductionmentioning
confidence: 99%